Monilinia species causing brown rot of peach in China. - Meng-Jun Hu; Kerik D Cox; Guido Schnabel; Chao-Xi Luo (PLoS ONE, 2011)
In this study, 145 peaches and nectarines displaying typical brown rot symptoms were collected from multiple provinces in China. A subsample of 26 single-spore isolates were characterized phylogenetically and morphologically to ascertain species. Phylogenetic analysis of internal transcribed spacer (ITS) regions 1 and 2, glyceraldehyde-3-phosphate dehydrogenase (G3PDH), β-tubulin (TUB2) revealed the presence of three distinct Monilinia species. These species included Monilinia fructicola, Monilia mumecola, and a previously undescribed species designated Monilia yunnanensis sp. nov. While M. fructicola is a well-documented pathogen of Prunus persica in China, M. mumecola had primarily only been isolated from mume fruit in Japan. Koch's postulates for M. mumecola and M. yunnanensis were fulfilled confirming pathogenicity of the two species on peach. Phylogenetic analysis of ITS, G3PDH, and TUB2 sequences indicated that M. yunnanensis is most closely related to M. fructigena, a species widely prevalent in Europe. Interestingly, there were considerable differences in the exon/intron structure of the cytochrome b (Cyt b) gene between the two species. Morphological characteristics, including spore size, colony morphology, lesion growth rate, and sporulation, support the phylogenetic evidence suggesting the designation of M. yunnanensis as a new species. A new multiplex PCR method was developed to facilitate the detection of M. yunnanensis and differentiation of Monilinia spp. causing brown rot of peach in China.